Pelaksanaan Kegiatan Ekstrakurikuler Drumband dalam Mengembangkan Bakat dan Minat Siswa di SMPN 38 Padang - Septriadi Hanri; Ardipal Ardipal (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the planning, implementation and impact of Drumband Extracurricular in developing students' talents and interests at SMP Negeri 38 Padang. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through observation, interviews and documentation. The steps of analyzing data are data condensation, data presentation and conclusion drawn. Based on the results of the presentation of data, it can be concluded that: the initial plan to hold a drumband extracurricular was due to the proposal of the student's guardian realized by the junior high school. The drumband extracurricular structure was selected through deliberation of all junior high school ranks. The members of the drumband are taken from grades 7 and 8 through selection. The implementation of drumband extracurricular activities every Saturday and Sunday morning. Before starting, condition the drumband members to get together. Then divide several groups according to musical instruments. The coach gave an example first, after that it was followed by students. After the practice is over, pray together and give motivation from the coach. The impact of drumband extracurricular activities on the development of students' talents and interests is that students can develop their talents and interests outside the classroom. Discipline to time and establish good cooperation between members. Students are more enthusiastic about learning about drumband musical instruments.